PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL ECOLINK DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS - Husain, Putra Ismail; PanaI, Abdul Haris; Arif, Rifda Mardian; Arifin, Irvin Novita; Arifin, Vicka Muniati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research aimed to develop a digital learning medium called Ecolink that meets the criteria of feasibility, practicality, and effectiveness in IPAS (Science, Social Studies, and Arts) learning to improve student learning outcomes on the topic of Environmental Changes and Waste Management at SDN 98 Kota Utara. This study employed the Research and Development (R&D) method, utilizing the ADDIE development model, which includes the stages of analyze, design, development, implement, and evaluate. Through validation by experts and users, the Ecolink digital learning medium obtained a recapitulation of average feasibility scores with a percentage of 94.6%, categorizing it as highly feasible for use by teachers and students in elementary schools. For the practicality test of the Ecolink digital learning medium, researchers used teacher observation sheets. The practicality percentage for using the Ecolink digital learning medium in learning reached 95%, which falls into the highly practical category. Regarding the effectiveness of the Ecolink digital learning medium during its implementation in Class V of SDN 98 Kota Utara, researchers administered a learning outcome test to measure its effectiveness. The total pretest score was 37.72%, while the total posttest score reached 85.90%. The N-Gain calculation showed a value of 0.77, which is categorized as